DESAIN APLIKASI GO-TRASH MENGGUNAKAN METODE DESIGN THINKING DAN VALUE PROPOSITION CANVAS - Bayu Zahran; Tiawan; Cepi Indra Grahana; Anwar Hilman; Lila Setiyani; Ahmad Najib Mutawally; Eni Nuraeni; Feris Andrian Chandra; Lulu Asti Humairah; Sarah Kartini (Program Studi Informatika Universitas Teknologi Sumbawa, 2024)
The Go-Trash application design aims to overcome the problem of waste management in urban areas with an innovative approach. The main problems include low public awareness and minimal information about waste sorting and recycling. Using the Design Thinking method, the team went through the stages of empathy, definition, ideation, prototyping, and testing to understand user needs. The Value Proposition Canvas is used to formulate the added value of the application, such as ease of waste sorting, recycling incentives, and real-time information about the nearest waste collection points. The output produced from this research is in the form of a Go-Trash application design which functions as a waste management tool as well as a platform for education and community empowerment. The app's main features include a waste sorting guide, a recycling incentive program, and notifications of waste collection locations and schedules. The resulting output is a reduction in the volume of waste going to landfill, increased recycling, and increased public awareness and participation. The Go-Trash application is expected to be an effective solution in creating a cleaner and healthier environment.